THE CORRELATION BETWEEN STUDENTS’ PERCEPTION OF READING LECTURER AND STUDENTS’ READING ACHIEVEMENT AT THE FOURTH SEMESTER STUDENTS OF UNIVERSITY OF ISLAM MALANG - Galih - Gunardi (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: One of the most crucial impressions in teaching reading comprehension was when the learner luxuriated in the reading experience. In another word, students' perceptions are formed not only by themselves, but also by their surroundings and motivational support, which might affect them in increasing their comprehension. This study applied quantitative method and the population was two classes of Reading 4A & 4B, totally 59 students as samples. In this point, the students would be assessed their Reading lecturers’ competences by filled out the questionnaire, and compared with their Reading final scores. The result indicated that the mean of students’ perception was 100.186 with standard deviation was 12.123 and Reading 4 final score was 82.694, then standard deviation is 12.360. The r observed of students’ perception and reading achievement was at .960 with P value .000. The level of significance of the P value was less than 0.05 or 0.000 < 0.05. Finally, there was significant correlation between students’ perception on the reading lecturers’ competences and students’ reading achievement of fourth semester in English Department at University of Islam Malang.Key Word: Correlation, Students’ Perception, Reading Lecturers' Competences, and Reading Achievement